2020
DOI: 10.1021/acssuschemeng.0c05564
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Silicon Purification by Alloying–Leaching Refining: A Comparative Study of Mg–Si, Ca–Si, and Ca–Mg–Si Systems

Abstract: In the present work, a comparative study of the silicon alloying–leaching purification process was carried out on the recently developed Mg–Si system, the Ca–Si system, and the novel ternary Ca–Mg–Si system. Insights were provided into the integrated process from aspects of thermodynamic assessment, microstructural analysis, experimental observation, computational simulation, and analytical modeling. The main silicide precipitates of the three Mg–Si, Ca–Si, and Ca–Mg–Si alloys studied were determined as Mg2Si,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…As a typical example of the commercialized process for UMG silicon production, the ELKEM solar process has been successfully developed and operated by REC Solar Norway in the past decade. The ELKEM solar process consists of a combination of metallurgical refining techniques including slag refining (Jakobsson, 2013;Thomas et al, 2021), acid leaching (Zhu et al, 2020b), and directional solidification (Ma et al, 2013;Ren et al, 2018) that upgrades the metallurgical-grade Si to solar-grade Si. In the slag refining step, B content in Si is reduced through oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical example of the commercialized process for UMG silicon production, the ELKEM solar process has been successfully developed and operated by REC Solar Norway in the past decade. The ELKEM solar process consists of a combination of metallurgical refining techniques including slag refining (Jakobsson, 2013;Thomas et al, 2021), acid leaching (Zhu et al, 2020b), and directional solidification (Ma et al, 2013;Ren et al, 2018) that upgrades the metallurgical-grade Si to solar-grade Si. In the slag refining step, B content in Si is reduced through oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of alumina crucibles may lead to an unwanted side reaction with Ca in the melt, consuming of the impurity getter, and introducing of Al impurity that contaminates the melt (Zhu et al, 2021), Meteleva-Fischer et al have highlighted the considerable influence of the cooling rate on the alloy microstructure and Recently, Mg has emerged as a novel and effective impurity getter for silicon purification owing to its similarly strong chemical affinity to P as compared to Ca. Moreover, while the leaching of the Si-Ca alloy generates the solid by-product siloxene, the leaching of Si-Mg is free of solid by-product and with higher Si recovery (Zhu et al, 2020b). However, the impact of cooling rates during solidification, a potentially significant factor, has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism is to dissolve the precipitates of the Si alloy in an acidic solution, and the remaining part is the dissolvable Si phase. To date, considerable work had been done on silicon purification through acid leaching of different Si alloy systems, including the binary system Si-Ca (Schei, 1985), Si-Mg (Espelien, Tranell and Safarian, 2017;Zhu, Azarov, et al, 2020;Zhu, Ying Yue, et al, 2020), Si-Al (Yoshikawa and Morita, 2003;Ban et al, 2015), and the ternary systems as the binary combinations (Zhu, Wan, et al, 2020). Sun et al(Sun et al, 2017) found that P enriched in the CaAl2Si2 phase in Si-30at%Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Taking the ELKEM solar process developed in Norway as an example, [4] around 60 pct energy consumption and 90 pct CO 2 emission can be reduced through the combination of metallurgical refining techniques, respectively, slag refining, acid leaching, and directional solidification. In the above refining techniques, slag refining [5][6][7] and acid leaching [8,9] are targeted for the removal of the most challenging impurities boron (B) and phosphorus (P) from the crude metallurgical-grade silicon (MG-Si).…”
Section: Introductionmentioning
confidence: 99%